2015
DOI: 10.2903/j.efsa.2015.4238
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety and efficacy of L‐tryptophan, technically pure, produced by Escherichia coli strains DSM 25084, KCCM 11132P or SARI12091203 for all animal species based on a dossier submitted by AMAC EEIG

Abstract: The product L‐tryptophan is a nutritional feed additive produced by fermentation using one of three strains of Escherichia coli. L‐Tryptophan produced by E. coli SARI12091203 could not be assessed because the data submitted did not permit the identity and safety of the strain, and the purity of the additive, to be determined. The EFSA Panel on Additives and Products or Substance used in Animal Feed (FEEDAP) could not conclude on the safety of this product for target animals, for consumers, users and the enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The applicant submitted a study on the shelf-life of the additive and a study on the stability of the additive in water for drinking performed with the additive under assessment. The rest of the stability studies (shelf-life at room temperature, stability in premixtures and in feedingstuffs and capacity to distribute homogeneously in premixtures and in pelleted feed) were performed with L-tryptophan produced by different E. coli strains (KCCM 80135 or KCCM 11132P) from the same producer (EFSA FEEDAP Panel, 2015b, 2019c. 36 As the production strains share a common lineage (E. coli K12 derivatives), the manufacturing process is the same and the product characteristics are very similar, the FEEDAP Panel considers that the stability and homogeneity studies performed with L-tryptophan of the other two production strains are indicative of the stability of the product under assessment.…”
Section: Stability and Homogeneitymentioning
confidence: 99%
“…The applicant submitted a study on the shelf-life of the additive and a study on the stability of the additive in water for drinking performed with the additive under assessment. The rest of the stability studies (shelf-life at room temperature, stability in premixtures and in feedingstuffs and capacity to distribute homogeneously in premixtures and in pelleted feed) were performed with L-tryptophan produced by different E. coli strains (KCCM 80135 or KCCM 11132P) from the same producer (EFSA FEEDAP Panel, 2015b, 2019c. 36 As the production strains share a common lineage (E. coli K12 derivatives), the manufacturing process is the same and the product characteristics are very similar, the FEEDAP Panel considers that the stability and homogeneity studies performed with L-tryptophan of the other two production strains are indicative of the stability of the product under assessment.…”
Section: Stability and Homogeneitymentioning
confidence: 99%
“…L-Tryptophan produced by Escherichia coli KCCM 11132P 5 L-Tryptophan produced by E. coli KCCM 11132P has been characterised in a previous scientific opinion (EFSA FEEDAP Panel, 2015).…”
Section: 1mentioning
confidence: 99%
“…In 2015, the FEEDAP Panel issued an opinion on the safety and efficacy of L-tryptophan produced by E. coli strains DSM 25084 or KCCM 11132P (EFSA FEEDAP Panel, 2015). The Panel concluded that the additives produced by E. coli strains DSM 25084 and KCCM 11132P do not give rise to safety concerns with regard to the genetic modifications of the production strain and that they are safe for non-ruminant target species when supplemented to diets in nutritionally appropriate amount, but should not be given to ruminants in an unprotected form because of the formation of skatole (3-methylindole) during ruminal fermentation.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations